2011
DOI: 10.1007/s00259-010-1700-1
|View full text |Cite
|
Sign up to set email alerts
|

Facile labelling of an anti-epidermal growth factor receptor Nanobody with 68Ga via a novel bifunctional desferal chelate for immuno-PET

Abstract: PurposeThe ∼15 kDa variable domains of camelid heavy-chain-only antibodies (called Nanobodies®) have the flexibility to be formatted as monovalent, monospecific, multivalent or multispecific single chain proteins with either fast or slow pharmacokinetics. We report the evaluation of the fast kinetic anti-epidermal growth factor receptor (EGFR) Nanobody 7D12, labelled with 68Ga via the novel bifunctional chelate (BFC) p-isothiocyanatobenzyl-desferrioxamine (Df-Bz-NCS). Df-Bz-NCS has recently been introduced as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 41 publications
7
74
1
Order By: Relevance
“…Second, the labels were poorly retained within cells after Ab internalization and catabolism. More recently, a novel bifunctional chelate (BFC) p-isothiocyanatobenzyl-DFO (Df-Bz-NCS), originally developed for 89 Zr labelling, was used to prepare anti-EGF Nanobody conjugates of DFO for 68 Ga labelling for PET applications [74]. Fast radiolabelling, high tumour uptake and tumour to normal tissue ratios in nude mice bearing A431 xenografts were obtained with the fast kinetics of the 68 Ga-Nanobody conjugates, indicating a promising application of DFO conjugates with 68 Ga.…”
Section: Desferrioxamine and Galliummentioning
confidence: 99%
“…Second, the labels were poorly retained within cells after Ab internalization and catabolism. More recently, a novel bifunctional chelate (BFC) p-isothiocyanatobenzyl-DFO (Df-Bz-NCS), originally developed for 89 Zr labelling, was used to prepare anti-EGF Nanobody conjugates of DFO for 68 Ga labelling for PET applications [74]. Fast radiolabelling, high tumour uptake and tumour to normal tissue ratios in nude mice bearing A431 xenografts were obtained with the fast kinetics of the 68 Ga-Nanobody conjugates, indicating a promising application of DFO conjugates with 68 Ga.…”
Section: Desferrioxamine and Galliummentioning
confidence: 99%
“…[517] Specifically, nanbobodies have been used as antagonistic drugs [518] and targeting agents of effector domains [519] in cancer immunotherapy. On the other hand, several molecular imaging modalities of SPECT [520] and PET, [521] optical imaging, [522] and ultrasound imaging [523] have been actively directed toward the target by means of nanobodies conjugated to them. Additionally, grafting nanobodies on nanoparticles have shown a considerable potential for increasing their affinity toward the target.…”
Section: Antibodiesmentioning
confidence: 99%
“…Among others, linking aHGF-Nanobodies to our recently described aEGFRNanobody 7D12 might be promising (17). Like other researchers postulated; combination therapies are needed to overcome acquired resistance to inhibitors of signal transduction pathways.…”
Section: Mol Cancer Ther; 11(4) April 2012mentioning
confidence: 99%
“…Initial biodistribution studies with monospecific anti-EGFR (aEGFR)-Nanobodies in tumor-bearing mice showed, as expected, rapid blood clearance with a serum half-life time of less than an hour and low tumor uptake (15)(16)(17). Therefore, monospecific Nanobodies do not seem to be qualified for long-term blockage of growth factors and their receptors.…”
Section: Introductionmentioning
confidence: 99%